PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ADOBE FLASH CS6 PADA TEMA 8 UNTUK KELAS V SD/MI - Astiamona, Umi Isma; Marli, Suhardi; Kartono, Kartono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis research aims to develop learning media based on Adobe Flash CS6 about socio-cultural material in Indonesia which are valid according to proficient media experts, material experts, and students. The research method used is the Borg and Gall model. The data sources of this study were two media experts, two material experts, as well as twelve VA grade students at SD Muhammadiyah 2 Pontianak. The research instruments used were interviews, pre-research, media expert validation questionnaire, material expert validation questionnaire, student assessment questionnaire. The data obtained are quantitative data and qualitative data. Quantitative data were obtained from expert validation questionnaires and questionnaires about students while qualitative data were obtained from interpretations of quantitative data. Quantitative data were analyzed by calculating the average score then published using a 1-5 Likert scale. The results showed the level of product validity according to media experts was very valid. The level of product validity according to the material experts is very valid. Then the level of product validity according to student level is very valid. So it can be concluded that this research produces Adobe Flash CS6-based learning media which is very valid according to media experts, material experts, and students.